Application of a tetrapyrimidyl cyclobutane synthesized in the organic solid state: a halogen-bonded supramolecular ladder. Issue 41 (7th October 2020) - Sinnwell, Michael A.; Santana, Carlos L.; Bosch, Eric; MacGillivray, Leonard R.; Groeneman, Ryan H.
Abstract : A supramolecular ladder sustained by halogen bonds with rungs based upon a photoproduct, namely rctt -tetrakis(5′-pyrimidyl)cylcobutane, generated in the solid state is reported. Abstract : A halogen-bonded supramolecular ladder comprised of a novel pyrimidine-based cyclobutane photoproduct synthesized in the organic solid state via a [2 + 2] photoreaction is reported. The photoproduct rctt -tetrakis(5′-pyrimidyl)cyclobutane functions as rungs while the linear divergent halogen-bond donor 1, 4-diiodoperchlorobenzene acts as the rails. Our report also confirms the structure and stereochemistry of the tetrapyrimidyl cyclobutane ring system.